KONSUMSI SUPLEMEN MAKANAN DAN FAKTORFAKTOR YANG BERHUBUNGAN PADA REMAJA SMA ISLAM AL - AZHAR 3 JAKARTA SELATAN TAHUN 2005 - Mery Ramadani (Andalas University, Faculty of Public Health, 2007)
Quality of human resource (SDM) is the one of primary factor that need to performed a national development. Nutrient aspects takes a vital role to get the best quality of human resources. Adolescent need to getting some specific attention because of they have been growth experience and develop physically (Growth Spurt) and mentally. With the rapid development and improvement in food product, nutrition, pharmacy and communication, has influenced the behavior and life style, including eating habit in adolescent. One of it is the consumption of supplements to improve the quality of adolescent's dietarry. This research aim to see proportion of sex, nutrient knowledge, nutrient status, physical activity, body image, parents's education, parents's occupation, parents's food supplements consumption, and related with adolescent's food supplements consumption in SMA Islam Al-Azhar 3 Jakarta Selatan.This research use the cross sectional method. Research population are, all adolescent of I class and II class which fulfill of criteria and amount to 173 person. The result showed 62,4% of adolescent consumes food supplements. As a result from bivariat analysis known that nutrient knowledge and parents's food supplements consumption have a meaning correlation with adolescent's food supplements consumption. While of sex, nutrient status, physical activity, body image, parents's education and parents's occupation showing meaningless correlation with adolescent's food supplements consumption. Base on result of these researches so it is suggested to parents and school side to give nutrition knowledge for adolescent. We also suggested adolescent consumes health menu better than food supplements to fulfill daily food intake.